2012
DOI: 10.1146/annurev-cellbio-101011-155807
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Troubles of Aneuploidy

Abstract: Deviation from a balanced genome by either gain or loss of entire chromosomes is generally poorly tolerated in all eukaryotic systems studied to date. Errors in mitotic or meiotic cell division lead to aneuploidy, which places a burden of additional or insufficient gene products from the mis-segregated chromosomes on the daughter cells. The burden of aneuploidy often manifests itself as impaired fitness of individual cells and whole organisms, where abnormal development is also characteristic. Yet, the vast ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
156
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(160 citation statements)
references
References 164 publications
(212 reference statements)
4
156
0
Order By: Relevance
“…Consistent with experiments in both C. albicans and S. cerevisiae (Chen et al 2004;Torres et al 2007;Forche et al 2008;Pavelka et al 2010;Abbey et al 2011;Siegel and Amon 2012), a significant correlation was observed between aneuploidy and longer doubling times, although not all aneuploid strains exhibited slow growth. A previous study noted a correlation between faster growth rates and increased virulence (MacCallum et al 2009), but this was not observed in the analysis of the 21 strains described here.…”
Section: Aneuploidy In C Albicanssupporting
confidence: 85%
See 1 more Smart Citation
“…Consistent with experiments in both C. albicans and S. cerevisiae (Chen et al 2004;Torres et al 2007;Forche et al 2008;Pavelka et al 2010;Abbey et al 2011;Siegel and Amon 2012), a significant correlation was observed between aneuploidy and longer doubling times, although not all aneuploid strains exhibited slow growth. A previous study noted a correlation between faster growth rates and increased virulence (MacCallum et al 2009), but this was not observed in the analysis of the 21 strains described here.…”
Section: Aneuploidy In C Albicanssupporting
confidence: 85%
“…These results are consistent with aneuploidy being associated with a general fitness defect in yeast species when grown in replete media (Torres et al 2007;Forche et al 2008;Pavelka et al 2010;Siegel and Amon 2012). In contrast, aneuploidy did not correlate with any other strain attributes including virulence (Supplemental Table S5).…”
Section: Substitution Rates and Evolutionary Selection In Clinical Issupporting
confidence: 80%
“…The observed patterns of gene duplicability are indeed consistent with the idea of the existence of a conserved core that needs to remain untouched ("single-copy" group) and the existence of processes that are more amenable to modifications and that might be responsible for adaptations to new environments and the evolution of distinct morphological features ("multicopy" group) (Kitano, 2004). Gene duplication in itself can indeed modulate gene function in a negative way and as such impact core gene function by, for instance, increasing absolute gene dosage of genes with strict gene expression constraints (Siegel and Amon, 2012) through the accumulation of mutations in duplicate copies with potential pleiotropic negative effects on wild-type fitness (Bridgham et al, 2008;Dean et al, 2008;De Smet et al, 2013;Kaltenegger and Ober, 2015) or potential cytotoxic effects (e.g., protein misfolding) (Zhang and Yang, 2015). As a result, duplicates of genes sensitive to these processes might be eradicated quickly, also after WGD.…”
Section: Discussionmentioning
confidence: 99%
“…Although strictly computational, it is estimated that 28% of mouse proteins are mostly disordered [50]. Based on empirical evidence, no less than 20% of encoded proteins are believed to exist in multisubunit assemblies [51], with increases in excess subunits in aneuploid cells as a result of gene-dosage imbalances [52].…”
Section: Drips Slips: All In the Rdp Familymentioning
confidence: 99%